LEGISLATIVE SUPPORT OF INDEPENDENT WORK OF STUDENTS IN THE INITIAL PROCESS OF HIGHER EDUCATIONAL INSTITUTIONS OF THE SECOND HALF OF XIX II BEGINNING OF XX CENTURY - Benera В.Є. (Pedagogy of Higher and Secondary Education, 2022)
The article reveals the general theoretical bases for students’ self-work in the educational process in higher educational institutions of Ukraine (the 2nd half of XIX – the beginning of XXI cent.). The legislative providing of pedagogical formation of Ukraine is considered in the second half of XIX – at the beginning of XXI item.